2017
DOI: 10.1093/jac/dkx150
|View full text |Cite
|
Sign up to set email alerts
|

Are moxifloxacin and levofloxacin equally effective to treat XDR tuberculosis?

Abstract: All mutations reduced fluoroquinolone activity, even those classified as susceptible according to phenotypic tests. High-dose levofloxacin is less effective than high-dose moxifloxacin against both fluoroquinolone-resistant and -susceptible M. tuberculosis strains in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…Fluoroquinolones exhibit considerable anti-TB activities, although some of them such as ciprofloxacin, ofloxacin, and levofloacin are presently recommended as second-line anti-TB agents by WHO [6]; these drugs such as moxifloxacin (MXFX) are potential first-line agents and are under study for this indication [7]. In general, MTB isolates expressing resistance to both INH and RIF are susceptible to fluoroquinolones, while MXFX retains activity against MTB strains with various levels of fluoroquinolones resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoroquinolones exhibit considerable anti-TB activities, although some of them such as ciprofloxacin, ofloxacin, and levofloacin are presently recommended as second-line anti-TB agents by WHO [6]; these drugs such as moxifloxacin (MXFX) are potential first-line agents and are under study for this indication [7]. In general, MTB isolates expressing resistance to both INH and RIF are susceptible to fluoroquinolones, while MXFX retains activity against MTB strains with various levels of fluoroquinolones resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…The pre-XDR and XDR-TB patients in this study were managed with regimens which contained levofloxacin. Previous studies have shown that in cases of levofloxacin resistance, moxifloxacin may be the preferred drug of choice since gyrA A90V mutation has a smaller effect on moxifloxacin activity [8,26]. Therefore, these patients could have benefited from a regimen containing Moxifloxacin if the specific resistance markers had been determined timely.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quinolones especially fluoroquinolones were widely used as antibiotics, and WHO has recommended some of fluoroquinolones including ciprofloxacin, ofloxacin, and levofloxacin as second‐line anti‐TB agents for the treatment of patients with resistance or intolerance to first‐line anti‐TB therapy . Furthermore, the fourth generation fluoroquinolone moxifloxacin is under phase III clinical trial as a potential first‐line anti‐TB agent . Therefore, hybridization of quinoline with isatin appears to be an attractive strategy to develop high effective anti‐TB agents.…”
Section: Isatin‐quinoline/quinolone Hybridsmentioning
confidence: 99%